Similarities and Differences between Indonesian and English Semantic: Implications in Teaching English Semantic to Students - Nur Fitria, Tira (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2025)
This research explores the semantic similarities and differences between Indonesian and English, focusing on their implications for teaching English semantics to students. It employs a descriptive qualitative approach to analyze both languages. The study reveals that English and Indonesian share fundamental parallels in how meaning is structured and conveyed. They exhibit commonalities in basic vocabulary, sentence structures following SVO order, and the use of modifiers, adjectives, adverbs, prepositions, borrowed vocabulary, numerical systems, days of the week, prepositions, question words, conjunctions, and common expressions. These similarities facilitate comprehension and communication between speakers but are accompanied by distinctions in grammar, pronunciation, idiomatic expressions, and cultural contexts that distinguish their linguistic identities. Conversely, semantic differences arise from the unique linguistic and cultural contexts of each language. Lexical gaps occur where concepts lack direct equivalents due to differing cultural norms and experiences. Cultural specificity influences terms tied to specific Indonesian practices, while technical terminology adapts from English with contextual nuances. Euphemisms, metaphors, pragmatics, and social norms also shape semantic interpretation differently, impacting communication and translation accuracy. Understanding these semantic similarities and differences is crucial in teaching English semantics. Recognizing similarities aids in knowledge transfer and faster learning, leveraging students' familiarity with their native language. Addressing differences requires detailed explanations to ensure accurate comprehension and contextual usage of English vocabulary and expressions.